Critical reflections on postgraduate andragogy from the points of view of a Kenyan student and an Australian academic. Issue 3 (4th May 2019) - Cunningham, Christine; Wandei, Eunice
ABSTRACT: In this paper, we use Critical Reflective Practice to give voice to the experience of a Kenyan teacher who travelled to Australia to undertake advanced coursework in leadership and inclusive education studies. It also reflects upon an Australian academic as she tries to be more culturally responsive in her andragogy when teaching, supervising and mentoring postgraduate international students. We use reflective practices over an extended period to lessen the power imbalance between them as academic supervisor and postgraduate student. This eventually allowed for the student to teach and the academic to learn; and together we here shed light on what it is like to study and teach within an Australian university that annually enrols 6000 students from more than 100 countries around the globe.